EXPRESSION LINES IN MONOPRINT - Muhammad Saifuttibyan (Saraswati)
There are several things that trigger the onset of an idea before creating a work of art. One of the factors that trigger it because of the desire and curiosity to try things that are still not widely understood by the author. The author had the idea that the incision line can be used as an expression of feeling, be it at the time felt sad, confused, or happy. The emergence of these feelings impression interpreted as expression lines. Expression lines can be visualized as a description of various personal experiences varied. For example, among others, to learn to create abstract artwork.The line can be used as a symbol of freedom of expression because the broadest line utilization is often not limited by anything particular form or are not intended to form a case. The line can be thick, thin can, scratched or etched spirit slowly can produce lines of different nature. Thus the character of the line can also be used to optimize the impression of rhythm. The line is also more dynamic than simply create forms that refer to certain objects realistically made​​. An idea can sometimes be obtained from the incision line. Specifically, this idea originated from the confusion swriters often feels a dat the moment. The line is two points are connected. In theart world is often the presence of a line is not only just as a line but sometimes as a symbol of the emotions expressed through theline, or more precisely called a scratch. Scratches or lines made ​​by an artist will give a different impression of psychological presented one a line. General line is a series of dots that are not limited. In this case there are at least two senses of the line of a line and the line in general. A line is a line that is a dynamic entity, containing an action or actions of the action because it is needed to create a line.  The line-  in-general can be interpreted as orientation, direction, motion, and energy. Nevertheless, the explicit understanding that the line usually refers to the direction of two-dimensional art such as painting or drawing. While the meaning of the expression is the disclosure or the express intent, idea, ideas, messages, opinions, statements, emotions, and feelings that arise in human action. Meaning of expression might also be regarded as a means of communication of one's feelings to others. The expression covers a wide range that can be felt and understood by human beings or society.